Economic Consequences of Mispredicting Utility - Bruno S. Frey; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2008)
A framework is proposed for organizing phenomena related to the (mis)prediction of utility, in particular neglecting adaptation. A categorization is introduced that accounts for asymmetries in misprediction. In decision-making, goods and activities satisfying extrinsic desires are more salient than those serving intrinsic needs. Accordingly, there is an overconsumption of the former compared to the latter. The theoretical analysis is consistent with econometric evidence on commuting choice using data on subjective well-being. People show substantial adaptation to a higher labor income but not to commuting. This may account for the finding that people are not compensated for the burden of commuting.
Keywords: A12; D11; D12; D84; I31; J22; 330; adaptation; extrinsic/intrinsic attributes; individual decision-making; misprediction; subjective well-being; time allocation; Entscheidungstheorie; Entscheidung; Lebensqualität; Zeitverwendung; Arbeitsangebot; Theorie; Verhalten